Analisis Profit Terhadap Return Perusahaan Manufaktur Indonesia dan Malaysia - Qurrota'ayun, Annisa; Kususmawati, Diah Ayu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The purpose of this study was to examine and analyze the effect of profitability variables on stock returns of manufacturing companies in Indonesia and Malaysia. Total sample in this study was 302 companies using purposive sampling method. Based on the results of statistical tests, it is shown that in Indonesia the independent variable that affects return is only EPS and size is not a control variable. In Malaysia, the variables that can have a significant effect on returns are only EVA and ROA, the size of the Malaysian sample cannot be used as a control variable. In the combined sample of Indonesia and Malaysia, the variable size can be used as a control and the variables that can have a significant positive effect are EPS and ROA.